MR evaluation of tuberous sclerosis: increased sensitivity with fluid-attenuated inversion recovery and relation to severity of seizures and mental retardation. - Takanashi, J; Sugita, K; Fujii, K; Niimi, H (American Journal of Neuroradiology, 1995)
PURPOSE To evaluate the utility and possible increased sensitivity of fluid-attenuated inversion recovery (FLAIR) images for the detection of tubers in patients with tuberous sclerosis, compared with standard T2-weighted images, and to evaluate whether the tubers are correlated with neurologic symptoms. METHOD We examined the number, size, and location of tubers in five tuberous sclerosis patients using T2-weighted and FLAIR images. Their intelligence quotients, ages at the onset of the first seizure, seizure types, and epileptic severity also were studied retrospectively. RESULTS The number of tubers observed ranged from 4 to 17 on T2-weighted images, and from 10 to 33 on FLAIR images. All the tubers, other than the myelination line on T2-weighted images, were remarkably demonstrated as high-intensity lesions on FLAIR images. No correlation was found between the neurologic outcome and the number, size, or location of tubers on FLAIR images. CONCLUSION FLAIR images were very sensitive for the detection of tubers, especially small subcortical ones, the number, size, and location of which are not related to the neurologic symptoms.